Digital phenotyping for classification of anxiety severity during COVID-19 - Nguyen, Binh; Ivanov, Martin; Bhat, Venkat; Krishnan, Sri (Frontiers in Digital Health, 2022)
COVID-19 has led to an increase in anxiety among Canadians. Canadian Perspectives Survey Series (CPSS) is a dataset created by Statistics Canada to monitor the effects of COVID-19 among Canadians. Survey data was collected to evaluate health and health-related behaviours. This work evaluates CPSS2 and CPSS4, which were collected in May and July of 2020, respectively. The survey data is composed of up to 102 questions. This work proposes the use of the survey data characteristics to identify the level of anxiety within the Canadian population during the first- and second-phases of COVID-19 and is validated with the use of General Anxiety Disorder (GAD)-7 questionnaire. Minimum redundancy maximum relevance (mRMR) is applied to select the top features to represent user anxiety and support vector machine (SVM) is used to classify the separation of anxiety severity. We employ SVM for binary classification with 10-fold cross validation to separate the labels of Minimal and Severe anxiety to achieve an overall accuracy of 94.77% and 97.35% for CPSS2 and CPSS4, respectively. After analysis, we compared the results of the first- and second-phases of COVID-19 and determined a subset of the features that could be represented as pseudo passive (PP) data. The accurate classification provides a proxy on potential onsets of anxiety to provide tailored interventions. Future works can augment the proposed PP data for a more detailed digital phenotyping.